Lipid‐Polymer Hybrid "Particle‐in‐Particle" Nanostructure Gene Delivery Platform Explored for Lyophilizable DNA and mRNA COVID‐19 Vaccines. (22nd July 2022) - Li, Zhongyu; Zhang, Xue‐Qing; Ho, William; Bai, Xin; Jaijyan, Dabbu Kumar; Li, Fengqiao; Kumar, Ranjeet; Kolloli, Afsal; Subbian, Selvakumar; Zhu, Hua; Xu, Xiaoyang
Abstract: SARS‐CoV‐2 has led to a worldwide pandemic, catastrophically impacting public health and the global economy. Herein, a new class of lipid‐modified polymer poly (β‐amino esters) (L‐PBAEs) is developed via enzyme‐catalyzed esterification and further formulation of the L‐PBAEs with poly(d, l ‐lactide‐coglycolide)‐ b ‐poly(ethylene glycol) (PLGA‐PEG) leads to self‐assembly into a "particle‐in‐particle" (PNP) nanostructure for gene delivery. Out of 24 PNP candidates, the top‐performing PNP/C12‐PBAE nanoparticles efficiently deliver both DNA and mRNA in vitro and in vivo, presenting enhanced transfection efficacy, sustained gene release behavior, and excellent stability for at least 12 months of storage at −20 °C after lyophilization without loss of transfection efficacy. Encapsulated with spike encoded plasmid DNA and mRNA, the lipid‐modified polymeric PNP COVID‐19 vaccines successfully elicit spike‐specific antibodies and Th1‐biased T cell immune responses in immunized mice even after 12 months of lyophilized storage at −20 °C. This newly developed lipid‐polymer hybrid PNP nanoparticle system demonstrates a new strategy for both plasmid DNA and mRNA delivery with the capability of long‐term lyophilized storage. Abstract : A "particle‐in‐particle" (PNP) nanostructure gene delivery platform is developed. The top‐performing PNP nanoparticle‐based delivery vector shows enhanced DNA and mRNA transfection efficacy in vitro and in vivo, sustained gene release behavior, and capability of long‐term lyophilization for storage. Furthermore, the lyophilized PNP COVID‐19 vaccines elicit strong immune responses in a BALB/c mouse model even after 12 months of storage.